The way forward: Malaysia-CLMV common higher education and research space - strategic linkages and exchanges - Abdullah, Nur Anisah; Ng, Melissa; Abdul Rahman, Shukran; Kaur, Sarjit (Institut Penyelidikan Pengajian Tinggi Negara, 2012)
The countries of Cambodia, Lao People’s Democratic Republic (PDR), Myanmar and Vietnam (CLMV) have always looked forward to establishing linkages and cooperation with Malaysia, especially in developing their human capital and institutional capacities (Ministry of Foreign Affairs, Malaysia, 2011). Malaysia, therefore, should capitalise on these positive gestures to pave inroads in broadening and deepening its liaisons with these neighbouring countries (Ministry of Foreign Affairs, Malaysia, 2011). At the diplomatic level, Malaysia and the CLMV countries have already established mutual understanding and are now progressively encouraging and creating greater collaboration in the academia (Aniswal & Munir, 2008). Through a series of dialogue workshops, which has been organised since 2008, the foundation for networking efforts and strategic linkages between Malaysia and the CLMV countries has been laid so as to strengthen the regional collaboration in higher education. The basic principle of collaboration and partnership between Malaysia and the CLMV countries is hinged on mutual respect. Malaysia’s gesture in providing assistance to the CLMV countries “rest[s] on equitable, conscientious and reciprocal engagement to enable the sharing of educational experience so that learning is a two-way process” (Ministry of Higher Education, Malaysia [MoHE], 2011: 23). In view of the fact that Malaysia shares a similar geographical identity and common traditions, values and developmental interests with the CLMV countries (as mentioned in the Malaysia- CLMV Collaboration chapter), her experiences in higher education is deemed to be more relevant and suitable in facilitating sustainable and transformative development of the higher education sector in these countries (MoHE, 2011).